Symptoms of Posttraumatic Stress and Sexual Concerns: The Intermediary Effects of Executive Functioning on Profiles of Youth Who Have Sexually Harmed. Issue 21 (November 2022) - Brown, Adam; Yoder, Jamie
There are demonstrated links in the general population between developmental adversity, associated trauma symptoms, and executive functioning difficulties in children and youth. However, research on links among these indicators and their relationship to antisocial behavior more broadly in samples of youth who have sexually harmed is only beginning to emerge. Some research indicates that intermediary factors like sexual concerns may be critical in understanding this population. This study explored relationships between trauma symptoms, sexual concerns, executive functioning, and their relationship to non-sexual delinquency in a sample of 196 youth who committed sexual harm. Structural equation modeling revealed numerous direct and indirect effects on the path to delinquency and that executive functioning plays a key role among those with serious sexual concerns. The results are contextualized and implications are discussed.